Tracing the Origin of Oxide Inclusions in Vacuum Arc Remelted Steel Ingots Using Trace Element Profiles and Strontium Isotope Ratios - Christoph Walkner; Gulnaz Mukhametzianova; Stefan Wagner; Jörg C. Korp; Andreas Graf; Johanna Irrgeher; Thomas C. Meisel; Thomas Prohaska (Metals)
Non-metallic inclusions (NMIs) in steel have a detrimental effect on the processing, mechanical properties, and corrosion resistance of the finished product. This is particularly evident in the case of macroscopic inclusions (>100 µm), which are rarely observed in steel castings produced using state-of-the-art technologies, whereby casting parameters are optimized towards steel cleanliness, and post-treatment steps such as vacuum arc remelting (VAR) are used, but frequently result in the rejection of the affected product. To improve production processes and develop effective countermeasures, it is essential to gain a deeper understanding of the origin and formation of NMIs. In this study, the potential of elemental and isotopic fingerprinting to trace the sources of macroscopic oxide NMIs found in VAR-treated steel ingots using SEM-EDX, inductively coupled plasma mass spectrometry (ICP-MS), laser ablation ICP-MS (LA-ICP-MS), and laser ablation multicollector ICP-MS (LA-MC-ICP-MS) were exploited. Following this approach, main and trace element content and 87Sr/86Sr isotope ratios were determined in two specimens of macroscopic NMIs, as well as in samples of potential source materials. The combination of the data allowed the drawing of conclusions about the processes leading to the formation of these inclusions. For both specimens, very similar results were obtained, indicating a common mechanism of formation. The inclusions were likely exogenous in origin and were primarily composed of calcium–aluminum oxides. They appeared to have undergone chemical modification during the casting and remelting process. The results indicate that particles from the refractory lining of the casting system most likely formed the macroscopic inclusions, possibly in conjunction with a second, calcium-rich material.